Exposure to foodborne and orofecal microbes versus airborne viruses in relation to atopy and allergic asthma: epidemiological study. Issue 7232 (12th February 2000) - Matricardi, Paolo M; Rosmini, Francesco; Riondino, Silvia; Fortini, Michele; Ferrigno, Luigina; Rapicetta, Maria; Bonini, Sergio
Abstract: Objective: To investigate if markers of exposure to foodborne and orofecal microbes versus airborne viruses are associated with atopy and respiratory allergies. Design: Retrospective case-control study. Participants: 240 atopic cases and 240 non-atopic controls from a population sample of 1659 participants, all Italian male cadets aged 17-24. Setting: Air force school in Caserta, Italy. Main outcome measures: Serology for Toxoplasma gondii, Helicobacter pylori, hepatitis A virus, measles, mumps, rubella, chickenpox, cytomegalovirus, and herpes simplex virus type 1; skin sensitisation and IgE antibodies to relevant airborne allergens; total IgE concentration; and diagnosis of allergic asthma or rhinitis. Results: Compared with controls there was a lower prevalence of T gondii (26% v 18%, P=0.027), hepatitis A virus (30% v 16%, P=0.004), and H pylori (18% v 15%, P=0.325) in atopic participants. Adjusted odds ratios of atopy decreased with a gradient of exposure to H pylori, T gondii, and hepatitis A virus (none, odds ratio 1; one, 0.70; two or three, 0.37; P for trend=0.000045) but not with cumulative exposure to the other viruses. Conversely, total IgE concentration was not independently associated with any infection. Allergic asthma was rare (1/245, 0.4%) and allergic rhinitis infrequent (16/245, 7%) among the participants (245/1659) exposed to at least two orofecal and foodborne infections ( H pylori, T gondii, hepatitis A virus). Conclusion: Respiratory allergy is less frequent in people heavily exposed to orofecal and foodborne microbes. Hygiene and a westernised, semisterile diet may facilitate atopy by influencing the overall pattern of commensals and pathogens that stimulate the gut associated lymphoid tissue thus contributing to the epidemic of allergic asthma and rhinitis in developed countries.